The Role Of Indian Judiciary In Development Of Principles On Narco Analysis And Polygraphy Test System (International Journal of Food and Nutritional Sciences, 2023)
The utilization of narcoanalysis and polygraphy examinations has been a topic of judicial scrutinyand deliberation in India. The Indian judiciary has been instrumental in establishing the standardsthat govern the acceptability and utilization of these tests in judicial procedures.